Preservation of Cells of the Organ of Corti and Innervating Dendritic Processes Following Cochlear Implantation in the Human: An Immunohistochemical Study - Kamakura, Takefumi (Otol Neurotol, 2018)
HYPOTHESIS: This study evaluates the degree of preservation of hair cells, supporting cells, and innervating dendritic processes after cochlear implantation in the human using immunohistochemical methods. BACKGROUND: Surgical insertion of a cochlear implant electrode induces various pathologic changes within the cochlea including insertional trauma, foreign body response, inflammation, fibrosis, and neo-osteogenesis. These changes may result in loss of residual acoustic hearing, adversely affecting the use of hybrid implants, and may result in loss of putative precursor cells, limiting the success of future regenerative protocols. METHODS: Twenty-eight celloidin-embedded temporal bones from fourteen patients with bilateral severe to profound sensorineural hearing loss and unilateral cochlear implants were studied. Two sections including the modiolus or basal turn from each temporal bone were stained using anti-neurofilament, anti-myosin-VIIa, and anti-tubulin antibodies in both implanted and unimplanted ears. RESULTS: INNER AND OUTER HAIR CELLS: Immunoreactivity was reduced throughout the implanted cochlea and in the unimplanted cochlea with the exception of the apical turn. DENDRITIC PROCESSES IN THE OSSEOUS SPIRAL LAMINA: Immunoreactivity was significantly less along the electrode of the implanted cochlea than in the other segments. INNER AND OUTER PILLARS, INNER AND OUTER SPIRAL BUNDLES, AND DEITERS’ CELLS: Immunoreactivity was similar in the implanted and unimplanted cochleae. CONCLUSIONS: Insertion of a cochlear implant electrode may significantly affect the inner and outer hair cells both along and apical to the electrode, and dendritic processes in the osseous spiral lamina along the electrode. There was less effect on pillar cells, Deiters’ cells, and spiral bundles.